Effect of inclusion rate of Fermenten on performance, carcass traits, and apparent total tract digestibility of growing Angus crossbred steers. (2nd December 2018) - Garcia-Ascolani, Mariana Eloisa; Schulmeister, Tessa M; Ruiz-Moreno, Martin; Henry, Darren D; Ciriaco, Francine M; Silva, Gleise M; Block, Elliot; Dubeux, Jose C B; Lamb, Graham C; DiLorenzo, Nicolas
Abstract: In Phase 1 (days 0 to 56) of a two-phase experiment, 81 steers (initial BW = 189 ± 22 kg) were arranged in a generalized randomized block design, allocated to nine pens (nine steers per pen) and assigned to one of three dietary treatments. Treatments consisted of different inclusion rates of Fermenten (FER ) in a backgrounding diet fed ad libitum, and were as follows: 0% (CON), 2%, or s FER in the diet DM. Steer was considered the experimental unit, and individual DMI was measured using the GrowSafe system. In Phase 2 (days 57 to 112), treatments were discontinued and steers were relocated to a paddock with free access to a common basal diet, to assess potential residual effects of FER. Effect of treatment was measured on performance, concentration of serum urea nitrogen (SUN ), NEFA and glucose, and apparent total tract digestibility of nutrients. On day 56, steers fed 4% FER had lesser ( P = 0.01) BW than 2% FER steers. Steers fed CON also tended ( P = 0.08) to have greater BW than 4% FER steers. ADG was not different ( P = 0.96) between CON and 2% FER steers, whereas steers in the 4% FER treatment had lesser ( P ≤ 0.01) ADG than CON and 2% FER. Steers in the 4% FER treatment had lesser ( P = 0.04) DMI than CON, and were less feed efficient ( P ≤ 0.04) than 2% FER and CON steers. However, DMI as a percentage of the BW did not differ ( P = 0.07) across treatments. A treatment effect was observed for final BW on day 112 ( P = 0.05), where 4% FER tended ( P = 0.07) to have lesser BW than CON. In Phase 2, ADG was not different ( P = 0.18) among treatments. However, overall ADG (days 0 to 112) was lesser ( P = 0.02) for steers fed 4% FER when compared with CON. There was no difference ( P ≥ 0.12) in longissimus muscle area gain or 12th rib fat depth gain. There was a treatment × day interaction for serum concentrations of glucose ( P < 0.001), NEFA ( P < 0.001), and SUN ( P < 0.001). Steers fed 4% FER had greater ( P < 0.001) DM, OM, NDF, ADF, and CP apparent total tract digestibility than CON. Similarly, 4% FER steers had greater ( P ≤ 0.02) DM, OM, NDF, and ADF digestibility than 2% FER. Results show that although inclusion of FER increased apparent total tract digestibility of nutrients, DMI and overall performance of growing beef cattle were negatively affected, mainly when FER was included at 4% of the diet DM.